PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH, KEPUASAN KERJA , DAN KOMITMEN ORGANISASI DALAM MENINGKATKAN KINERJA GURU SEKOLAH DASAR DI KECAMATAN SANGIA AMBULU KABUPATEN BUTON - Abidin - (JI@P, 2015)
Abidin, 2015. “Influence of headmaster’s leadership style, work satisfaction,and organizational commitment toward Elementary School Teachers’performances in Sangia Wambalu Sub District Buton Regency”. Slamet RiyadiUniversity, Thesis, unpubllshed.The improvement of teachers’ performances is desirable in the attempt ofsupporting the achievement of high-quality education. The problem occurringin elementary schools in Education Office Technique Service Unit (UPTD) ofSangia Wambulu Sub District is that the overall teachers’ performances havenot met expectation, as indicated by the students’ lower learning outcome andthe teachers’ poor performance assessment result. Ermaya Suradinata statedthat performance is defined as the work outcome affected by background,cultural environment, skill and knowledge. For a teacher, a good work cultureenvironment can strengthen his/her motivation to achieve maximumperformance. To achieve the higher performance, the headmaster’sleadership in guiding, directing, and governing a school is a part of jobmotivation necessary to have. The teachers’ job satisfaction is a veryimportant factor to get optimum performance. The teachers’ organizationalcommitment is also a very important element of work attitude. The higher theorganizational commitment, the higher is the teachers’ sense of belonging tothe school and the higher is their performance. This research aimed to findout: (1) the effect of headmaster’s leadership upon teacher performance, (2)the effect of job satisfaction upon teacher performance, (3) the effect oforganizational commitment toward teacher performance, and (4) the effect ofheadmaster leadership style, job satisfaction, and organizational commitmentsimultaneously on the teacher performance. The samples of research werethe teachers of Elementary Schools in Education UPTD of Sangia WambuluSub District of Buton Regency, consisting of 43 respondents. Technique ofcollecting data used was questionnaire that had been tested for its validity andreliability. Technique of analyzing data used included partial correlational, t-,multiple correlation, and F-tests. The result of hypothesis testing showed that(1) there was a positive significant effect of headmaster leadership style onteacher performance; (2) there was a positive significant effect of jobsatisfaction on teacher performance; (3) there was a positive significant effectof organizational commitment on teacher performance; and (4) there was apositive significant effect of headmaster’s leadership style, job satisfaction,and organizational commitment simultaneously on teachers’ performances.The implication of research finding was that the performance of ElementarySchool teachers in Sangia Wambulu Sub District would be improved whenthere were good headmaster leadership style, higher job satisfaction andorganizational commitment.Keywords: leadership style, job satisfaction, organizational commitment, teacherperformance.